Urban daily labour markets in Gujarat, Western India - Bharati, Kanchan; Lobo, Lancy; Kumar, Dhananjay (London Routledge, 2024)
This volume explores one of the most complex labour landscapes of India - the urban daily labour market. These markets form an important sector of the urban informal labour market and contribute significantly to the Indian economy. This book presents an empirical, comparative picture of daily labour markets, in Gujarat, Western India.
Keywords: Urban Economics; Demography; Labour Economics